Allopurinol Induction on Histopathological Structure of the Liver in Male Mice (Mus musculus) - Lestari, Dian Fita; Fatimatuzzahra, Fatimatuzzahra; Sianipar, Agnes Petra; Wulansari, Shahnaz Shabrina (Jurnal Biodjati, 2022)
Allopurinol is used to reduce total uric acid levels in the body into oxypurinol which can inhibit xanthine oxidase. Allopurinol inhibits the precursors of uric acid formation, xanthine, and hypoxanthine. However, consumption of the drugs can cause side effects on the liver. The aim of the research was to determine the effect of allopurinol induction on the liver histopathology of male mice (Mus musculus) DDY strain. The method used in this research was an experimental design used post-test only that was divided into 4 groups of 4 mice per group. The control group (P0) was given 0.5% Na-CMC, and groups I, II, and III (P1, P2, and P3) were induced by allopurinol at 10 mg/kg BW, 20 mg/kg BW, and 30 mg/kg BW for 14 days. Allopurinol induction was performed by oral gavage. The results of the research showed that treatment with allopurinol caused changes in the mice’s body weight, liver index, liver morphology, and histological structure of the liver tissue, including necrosis, steatosis, leukocyte infiltration, binuclear hepatocytes, hepatocyte swelling, congestion, sinusoid dilatation, and hemorrhage. The level of liver damage increased in line with the dose used. This research indicated that the higher the allopurinol level, the higher the level of alteration in the liver section structure. Long-term use of allopurinol can cause damage to the structure of mice liver (liver toxicity).